2021
DOI: 10.1111/jce.14892
|View full text |Cite
|
Sign up to set email alerts
|

Protocol driven periprocedural anticoagulation for left atrial ablation

Abstract: Introduction A weight‐based heparin dosing policy adjusted for preprocedural oral anticoagulation was implemented to reduce the likelihood of subtherapeutic dosing during left atrial catheter ablation procedures. We hypothesized that initiation of the protocol would result in a greater prevalence of therapeutic activated clotting time (ACT) values and decreased time to therapeutic ACT during left atrial ablation procedures. Methods A departmental protocol was initiated for which subjects received intravenous u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The sample size is similar to other published reports but does limit the results. 14 , 15 , 16 , 17 The number of patients on each of the 4 preprocedural oral anticoagulants studied here is small—especially dabigatran—making the results less generalizable. When the ACT did drop below goal, the time below goal did decrease using the algorithm, but it was not a statistically significant decrease.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The sample size is similar to other published reports but does limit the results. 14 , 15 , 16 , 17 The number of patients on each of the 4 preprocedural oral anticoagulants studied here is small—especially dabigatran—making the results less generalizable. When the ACT did drop below goal, the time below goal did decrease using the algorithm, but it was not a statistically significant decrease.…”
Section: Discussionmentioning
confidence: 96%
“…In 89 patients on NOACs, Payne and colleagues 14 found that 29% of ACTs were therapeutic when using an initial bolus of 120 U/kg and increased to 49% when the initial bolus was increased to 150 U/kg. Bradley and colleagues 16 reported that a protocol-guided approach that accounted for preprocedure oral anticoagulant and weight-based dosing did increase the proportion of therapeutic ACT on first draw to 76.6%, from 57.7%, and decreased the average time to therapeutic ACT to 30 minutes; however, supratherapeutic ACT on first draw (>400 seconds) increased from 6.4% to 18.2%. Safani and colleagues 17 reported impressive results using a comprehensive weight-adjusted, weight-based protocol that demonstrated a time to ACT >300 seconds of 14.6 minutes in 99 patients on NOACs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations